STRATEGI KOMUNIKASI KORPORAT DALAM MENINGKATKAN BRAND AWARENESS (STUDI KASUS PADA PT SEVAL LITERINDO KREASI) - DJUANDANILSYAH, DJUANDANILSYAH (GANEC SWARA, 2024)
This research aims to investigate the influence of three dimensions of corporate communication management (internal, external, and digital communication) on the enhancement of brand awareness of PT Seval Literindo Kreasi. Purposive sampling method was employed to select 30 respondents who are employees of the company. Data were collected through questionnaires and analyzed using validity test, reliability test, T-test, and multiple regression analysis. The findings indicate that internal, external, and digital communication have a positive and significant impact on improving brand awareness. Managerial implications and recommendations are discussed to enhance corporate communication strategies and brand awareness of the company